The Effect of Internal Control and Good Government Governance on Fraud Prevention - Sarah Andini; La Ode Anto; Nitri Mirosea (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Fraud remains a critical issue in public sector organizations, undermining accountability, transparency, and public trust in government institutions. Strengthening internal control systems and implementing Good Government Governance are widely regarded as essential strategies for preventing fraudulent practices. This study aims to examine the effect of internal control and Good Government Governance on fraud prevention in the public sector. Employing a quantitative research design, data were collected through structured questionnaires distributed to Government Internal Supervisory Apparatus at the Regional Inspectorate of South Konawe Regency, Indonesia. The data were analyzed using multiple linear regression supported by classical assumption testing. The findings indicate that internal control has a positive and significant effect on fraud prevention, demonstrating its role in minimizing opportunities for fraud through effective supervision and control mechanisms. In addition, Good Government Governance positively influences fraud prevention by promoting transparency, accountability, and ethical conduct within public institutions. These results confirm that the integration of robust internal control systems and sound governance practices is crucial for enhancing fraud prevention efforts. This study contributes to the public sector fraud prevention literature by providing empirical evidence that reinforces the importance of governance and control mechanisms in strengthening integrity and reducing fraud risks.